Economic, political and security imperatives in Xi Jinping's third term - Kam, Stefanie (2022)
As Xi Jinping secures a historic third term at the 20ᵗʰ Party Congress, China’s foreign policy objectives in the years ahead will be driven by economic, political and security initiatives shaped by both domestic and international political determinants.